Comparison of ultrasonography and positive contrast cystography for detection of urinary bladder disorders in dogs - Gallatti, Luciana Bastos; Iwasaki, Masao (Brazilian Journal of Veterinary Research and Animal Science, 2004)
Imaging techniques are often of great value in detecting lower urinary tract abnormalities in small animals, which frequently affect the urinary bladder. Survey and contrast radiography and ultrasonography allow evaluation of bladder shape, position and internal anatomy. The objective was to compare the frequence of identification of urinary bladder lesions in dogs using ultrasonography and positive contrast cystography and, also, determine the efficacy of these imaging procedures in indicating diagnostic hipothesis. This prospective study consisted of 35 dogs, males and females, from different breeds and ages, referred to Imaging Diagnostic Service of Veterinary Teaching Hospital (Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo) with clinical signs suggestive of bladder diseases. The positive contrast cystography was more efficient in detecting mucosal surface irregularity, bladder displacement and intraluminal structures except calculi. The ultrasonography identified more often uroliths and bladder wall thickening. Diverticula and bladder rupture were demonstrated only by contrast radiography and urinary sludge by sonographic exam. Intraluminal gas presence, related to emphysematous cystitis, was observed by both techniques. In 23 of 35 cases (65,7%) both of techniques were necessary to provide a complete diagnostic and in 12 cases (34,3%) the perform of just one kind of exam could indicated the diagnostic hipothesis.